Spectrophotometric determination of nateglinide in bulk and tablet dosage forms - Jain, Suresh; Bhandari, Anil; Purohit, Suresh (Asian Journal of Pharmaceutics (AJP), 2014)
Nateglinide (NTG) is available as tablet dosage form in 60 mg and 120 mg strength. In the present study, two simple, reproducible and efficient UV spectrophotometric methods for the estimation of this drug in bulk and pharmaceutical dosage forms have been developed. In method I, methanol-AR was used as solvent, while in method II, Methanolâ€AR + 10% V/V 3N NaOH was used as reference solvent. In method I, nateglinide shows Î»max at 216 nm, which is then shifted to 225.4 nm on increasing the basicity of the reference solvent in method II.The linearity for nateglinide was observed to be statistically in the range of 10-100 Î¼g/ml in method I and 100-1000 Î¼g/ml in method II. Both the methods were validated using ANOVA. The recovery studies confirmed the accuracy of the proposed methods.